DETERMINAN KEPEMILIKAN JAMINAN KESEHATAN NASIONAL (JKN) PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS GROBOGAN KABUPATEN GROBOGAN - Ervi Ummi Nadhiroh; Fitni Indrawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
In October 2020, the achievement of universal health coverage (UHC) IN Grobogan district only reached 72,03%. Grobogan Public Health Center is the health center with the lowest membership coverage, which only reached 56,4%. The purpose of this study is to determine the determinants of ownership of the National Health Insurance (JKN) in the citizen of the working area in Grobogan Public Heal;th Center, Grobogan Regency. The type of research is observational analytic with cross sectional design. The technique used is purposive sample sampling technique, with a total of 106 respondents. Chi square statistical test are used as instrument in the form of questionnaires and data analysis. The results show that the determinant of JKN ownership of the citizen of Grobogan Regency are education level (p 0,001), knowledge level (p 0,001), employment status (p 0,015), income level (p 0,001), information (p 0,001), and family support (p 0,001). While disease history (p 0,104), number of family (p 0,767), and health service seeking patterns (p 0,423) are not determinants of JKN ownership in the community. It is necessary to spread the information about the JKN program through socialization and the selection of appropriate information methods.